Awe Sparks Prosociality in Children - Stamkou, Eftychia; Brummelman, Eddie; Dunham, Rohan; Nikolic, Milica; Keltner, Dacher (Psychological Science, 2023)
Rooted in the novel and the mysterious, awe is a common experience in childhood, but research is almost silent with respect to the import of this emotion for children. Awe makes individuals feel small, thereby shifting their attention to the social world. Here, we studied the effects of art-elicited awe on children’s prosocial behavior toward an out-group and its unique physiological correlates. In two preregistered studies (Study 1: N = 159, Study 2: N = 353), children between 8 and 13 years old viewed movie clips that elicited awe, joy, or a neutral (control) response. Children who watched the awe-eliciting clip were more likely to spend their time on an effortful task (Study 1) and to donate their experimental earnings (Studies 1 and 2), all toward benefiting refugees. They also exhibited increased respiratory sinus arrhythmia, an index of parasympathetic nervous system activation associated with social engagement. We discuss implications for fostering prosociality by reimagining children’s environments to inspire awe at a critical age.